Human Embryonic Stem Cell Therapy in Crohn’s Disease: A Case Report - Shroff, Geeta (Am J Case Rep, 2016)
Patient: Male, 21 Final Diagnosis: Crohn’s disease Symptoms: Intolerance to specific foods • abdominal pain and diarrhea Medication: Human embryonic stem cell therapy Clinical Procedure: Human embryonic stem cell transplantation Specialty: Gastroenterology OBJECTIVE: Unusual or unexpected effect of treatment BACKGROUND: Crohn’s disease is a chronic inflammatory disease of the intestines, mainly the colon and ileum, related with ulcers and fistulae. It is estimated to affect 565 000 people in the United States. Currently available therapies, such as antibiotics, thiopurines, and anti-tumor necrosis factor-alpha agents, are only observed to reduce the complications associated with Crohn’s disease and to improve quality of life, but cannot cure the disease. Stem cell therapy appears to have certain advantages over conventional therapies. Our study aimed to evaluate the efficacy of human embryonic stem cell therapy in a patient with Crohn’s disease. CASE REPORT: A 21-year-old male with chief complaints of intolerance to specific foods, abdominal pain, and diarrhea underwent human embryonic stem cell therapy for two months. After undergoing human embryonic stem cell therapy, the patient showed symptomatic relief. He had no complaints of back pain, abdominal pain, or diarrhea and had improved digestion. The patient had no signs and symptoms of skin infection, and had improved limb stamina, strength, and endurance. The condition of patient was stable after the therapy. CONCLUSIONS: Human embryonic stem cell therapy might serve as a new optimistic treatment approach for Crohn’s disease.